White matter microstructure alterations in primary dysmenorrhea assessed by diffusion tensor imaging - Liu, Peng (Sci Rep, 2016)
Primary dysmenorrhea (PDM), a significant public health problem for adolescents and young women, is characterized by painful menstrual cramps. Recent neuroimaging studies have revealed that brain functional and structural abnormalities are related to the pathomechanism of PDM. However, it is not clear whether there are white matter (WM) alterations in PDM. We analyzed diffusion tensor imaging data from 35 patients and 35 healthy controls (HCs) matched for age and handedness. Tract-based spatial statistics and probabilistic tractography were used to measure integrity of WM microstructure. Compared to HCs, patients had increased fractional anisotropy (FA) along with decreased mean diffusivity (MD) and radial diffusivity (RD) in the corpus callosum (CC), superior longitudinal fasciculus (LF), corona radiata (CR), internal capsule (IC) and external capsule (EC). The FA of the splenium CC and right IC positively correlated with PDM duration while FA of the right anterior CR positively correlated with PDM severity in patient group. These WM tracts were found to show connections to other brain regions implicated in sensoimotor, affective, cognitive and pain processing functions through tractography. These findings provide preliminary evidence for WM microstructure alterations in PDM, which is potentially valuable for understanding pathomechanism of PDM.